Elaboração de um queijo tipo coalho condimentado com manjericão e alho - Ferraresso Junior, José Felipe (2018)
Milk is an emulsion that contains water, proteins, minerals, vitamins and lipids. It serves as the first kind of food for mammals which is the main characteristics of Mammalia class. Due its characteristics milk is the raw material of many product such as fermented milk, butter, cheeses among others and can be used as ingredient in various culinary preparations. Among the dairy products, cheeses represent a high volume of production. In Brazil, different kinds of cheeses are produced, like the coalho cheese, from Brazilian Northeastern which is widely consumed as grilled or as ingredients in recipes. This cheese is basically made with milk, rennet and salt, although, according the current legislation it may or may not contain added condiments or other ingredients. The objective of this work was to elaborate a coalho cheese spiced with basil. The physical-chemical parameters, instrumental texture profile and sensorial attributes were also evaluated. The cheese was made from whole bovine milk, type A which contains 3.5% of fats, a density of 1.0318 g/cm³ and acidity of 0.15% in lactic acid and the final product presented a total acidity of 0.18% (in lactic acid) mineral content, 4.79% and crude protein content of 15.91%. The humidity of 50.37% which classifies the product as high moisture cheese and soft mass and fat content of 13.51%, classifies the cheese as lean. Sensorial Analysis shows us that the high acceptance, 85±0.84% and the purchase intention, 83±0.74%. In the Word Association technique were listed categories as: good, green, innovation, herbal among others very positive which confirms the acceptance of the products by the consumers. The instrumental Texture Profile Analysis (TPA) was performed and parameters as hardness and springness were similar with values frm the literature, and chewiness and cohesiveness were below, showing that the cheese itself has a characteristic hardness and elasticity and soft curd, acording to the humidity classification.